Vitamin K: The coagulation vitamin that became omnipotent - Cranenburg, Ellen C. M.; Schurgers, Leon J.; Vermeer, Cees (Thrombosis and Haemostasis, 2007)
Vitamin K, discovered in the 1930s, functions as cofactor for the post-translational carboxylation of glutamate residues. Gammacarboxy glutamic acid (Gla)-residues were first identified in prothrombin and coagulation factors in the 1970s; subsequently, extra-hepatic Gla proteins were described,including osteocalcin and matrix Gla protein (MGP). Impairment of the function of osteocalcin and MGP due to incomplete carboxylation results in an increased risk for developing osteoporosis and vascular calcification, respectively, and is an unexpected side effect of treatment with oral anticoagulants. It is conceivable that other side effects, possible involving growth-arrest-specific gene 6 (Gas6) protein will be identified in forthcoming years. In healthy individuals, substantial fractions of osteocalcin and MGP circulate as incompletely carboxylated species, indicating that the majority of these individuals is subclinically vitamin K-deficient. Potential new application areas for vitamin K are therefore its use in dietary supplements and functional foods for healthy individuals to prevent bone and vascular disease, as well as for patients on oral anticoagulant treatment to offer them protection against coumarin-induced side effects and to reduce diet-induced fluctuations in their INR values.
Keywords: Vitamin K; matrix Gla protein; osteocalcin; oral anticoagulants; diagnostics